3D-printed polymer composite devices based on a ferroelectric chiral ammonium salt for high-performance piezoelectric energy harvesting - Sahoo, Supriya; Kothavade, Premkumar Anil; Naphade, Dipti R.; Torris, Arun; Praveenkumar, Balu; Zareba, Jan K.; Anthopoulos, Thomas D.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Materials Horizons, 2023)
Three-dimensional printing (3DP) is an emerging technology to fabricate complex architectures, necessary to realize state-of-the-art flexible and wearable electronic devices. In this regard, top-performing devices containing organic ferro- and piezoelectric compounds are desired to circumvent significant shortcomings of conventional piezoceramics, e.g. toxicity and high-temperature device processibility. Herein, we report on a 3D-printed composite of a chiral ferroelectric organic salt {[Me3CCH(Me)NH3][BF4]} (1) with a biodegradable polycaprolactone (PCL) polymer that serves as a highly efficient piezoelectric nanogenerator (PENG). The ferroelectric property of 1 originates from its polar tetragonal space group P4(2), verified by P-E loop measurements. The ferroelectric domain characteristics of 1 were further probed by piezoresponse force microscopy (PFM), which gave characteristic `butterfly' and hysteresis loops. The PFM amplitude vs. drive voltage measurements gave a relatively high magnitude of the converse piezoelectric coefficient for 1. PCL polymer composites with various weight percentages (wt%) of 1 were prepared and subjected to piezoelectric energy harvesting tests, which gave a maximum open-circuit voltage of 36.2 V and a power density of 48.1 mu W cm(-2) for the 10 wt% 1-PCL champion device. Furthermore, a gyroid-shaped 3D-printed 10 wt% 1-PCL composite was fabricated to test its practical utility, which gave an excellent output voltage of 41 V and a power density of 56.8 mu W cm(-2). These studies promise the potential of simple organic compounds for building PENG devices using advanced manufacturing technologies.